Thyroid-stimulating Hormone and Insulin Resistance: Their Association with Polycystic Ovary Syndrome without Overt Hypothyroidism - Cristina Laguna Benetti-Pinto; Vanessa Berini Piccolo; Daniela Angerame Yela; Heraldo Garmes (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Objective This study analyzed the effectiveness of the thyroid-stimulating hormone (TSH) as a predictor of insulin resistance (IR) and its association with the clinical and metabolic parameters of women with polycystic ovary syndrome (PCOS) without overt hypothyroidism. Study Design A cross-sectional study was performed. Women with PCOS and without overt hypothyroidism (n = 168) were included. Methods Receiver operating characteristic (ROC) curve was used to determine the cut-off point for TSH that would maximize sensitivity and specificity for a diagnosis of IR using homeostatic model assessment of insulin resistance (HOMA-IR)≥ 2.71. Clinical and metabolic parameters were compared as a function of the TSH cut-off limit and the presence of IR. Results Thyroid-stimulating hormone ≥ 2.77 mIU/L was associated with a diagnosis of IR, with sensitivity of 47.9% and specificity of 65.3%. There were no differences in clinical, hormonal or metabolic parameters between TSH < 2.77 and TSH of 2.77 - 10 mIU/L. Conclusion In women with PCOS without overt hypothyroidism, TSH ≥2.77 mIU/L is associated with IR; however, with poor sensibility, showing TSH to be a poor predictor of IR in this population. No clinical or metabolic alterations were found that would justify a change in clinical management. Thus, the IR should be investigated in all women with PCOS irrespective of TSH level.